2014
DOI: 10.1159/000355775
|View full text |Cite
|
Sign up to set email alerts
|

Is Alcohol Drinking Associated with Renal Impairment in the General Population of South Korea?

Abstract: Background/Aims: We examined relationships between the average amount of daily alcohol intake, drinking patterns, and renal dysfunction among South Korean adultsaged ≥ 20 years. Methods: The analysis used data from the Korean National Health and Nutrition Examination Survey (KNHANES), a cross-sectional survey of Korean civilians, conducted from January to December 2011. In this study, a sample of 5,251 participants was analysed. Results: Compared with abstinence, the odds ratio for a decrease in estimated glom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 37 publications
2
11
1
Order By: Relevance
“…White et al [74] found that ethanol intake has an inverse, approximately linear, relationship with the risk of onset of eGFR <60 mL/min/1.73 m 2 . The same relationship between frequency of drinking and CKD is also found in healthy Japanese, Koreans [7,9,16,78,79], and others [73,8082]. The same result also was confirmed among both African and Caucasian men and women.…”
Section: Association Between Alcohol Consumption and Chronic Kidney Dsupporting
confidence: 74%
“…White et al [74] found that ethanol intake has an inverse, approximately linear, relationship with the risk of onset of eGFR <60 mL/min/1.73 m 2 . The same relationship between frequency of drinking and CKD is also found in healthy Japanese, Koreans [7,9,16,78,79], and others [73,8082]. The same result also was confirmed among both African and Caucasian men and women.…”
Section: Association Between Alcohol Consumption and Chronic Kidney Dsupporting
confidence: 74%
“…No causal interpretation can be attached to this finding, although the same association has been reported in earlier studies; see, for example, Kim et al. (). A possible explanation is that patients with worse kidney health are more likely to abstain from alcohol; persistent nausea is a common symptom of seriously impaired kidney function.…”
Section: Discussionsupporting
confidence: 59%
“…Although baseline covariate effects were not of direct interest in this study, it is notable that alcohol consumption, as a binary factor, was associated with 5.5% better kidney function at study entry compared with abstainers. No causal interpretation can be attached to this finding, although the same association has been reported in earlier studies; see, for example, Kim et al (2014). A possible explanation is that patients with worse kidney health are more likely to abstain from alcohol; persistent nausea is a common symptom of seriously impaired kidney function.…”
Section: Discussionmentioning
confidence: 48%
“…This is in agreement with the findings of a previous study that found a significant association with alcohol consumption and renal impairment in the general population of South Korea. 51 On the contrary, some studies have reported no association between alcohol consumption and KD. 16,52…”
Section: Discussionmentioning
confidence: 99%